Respostas
respondido por:
3
Zero da função é você substituir o y=0
a) 4x-48=0
4x=48
x=48/4
x=12
b) 11x+121=0
11x=-121
x=-121/11
x=-11
c) 2x-28=0
2x=28
x=28/2
x=14
a) 4x-48=0
4x=48
x=48/4
x=12
b) 11x+121=0
11x=-121
x=-121/11
x=-11
c) 2x-28=0
2x=28
x=28/2
x=14
respondido por:
0
A)
y = 4x - 48
0 = 4x - 48
4x - 48 = 0
4x = 48
x = 48/4
x = 12
*********************
b)
y = 11x + 121
0 = 11x + 121
11x +121 = 0
11x = - 121
x = - 121/11
x = - 11
********************
c)
y = 2x - 28
0 = 2x - 28
2x - 28 = 0
2x = 28
x = 28/2
x = 14
*******************************
y = 4x - 48
0 = 4x - 48
4x - 48 = 0
4x = 48
x = 48/4
x = 12
*********************
b)
y = 11x + 121
0 = 11x + 121
11x +121 = 0
11x = - 121
x = - 121/11
x = - 11
********************
c)
y = 2x - 28
0 = 2x - 28
2x - 28 = 0
2x = 28
x = 28/2
x = 14
*******************************
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás